(untitled) (Proceedings of the Mongolian Academy of Sciences, 2019)
Ulaanbaatar, the capital of Mongolia, shows a highly dynamic urban and industrial development, with a strong increase of population. Thus, water demand is continuously rising while water availability is in general low and less reliable. The semi-arid and cold environment shows a high variability in precipitation and river discharge, with a general tendency towards decreasing water availability due to increasing air temperatures and thus rising potential evaporation. In parallel with the city’s development, the extended groundwater aquifer shows a clear decline, and the groundwater levels drop significantly. Therefore, a groundwater management system based on managed aquifer recharge is proposed and a strategy to implement these measures in the Tuul valley is presented. In this study considered enhancement of natural recharge rates during the early winter cold period, an increase of groundwater recharge through creating ice storages, due to keep water source as in ice form on surface. In dry season March to May ice storage recharge surface and groundwater by melting where Tuul River is non-flow condition. In this paper also written matlab icing code in water supply wells location, limited and unlimited area. The study of icing was processed in feflow simulation scenarios for artificially recharging groundwater resources. In this study considered feflow simulation scenarios for artificially recharging groundwater resources like enhancement of natural recharge rates during the early winter cold period, an increase of groundwater recharge through creating ice storages, due to keep water source as in ice form on surface, drainage canal recharging aquifer from opposite side, constructing underground dam that accumulates groundwater behind. The result shown that one of the possibilities recharge groundwater in dry season is icing method which creates ice sheets over ice and build ice storages in winter, keep water in ice form.